RESOURCE ADEQUACY AND UTILIZATION FOR TEACHING AND LEARNING EFFECTIVENESS IN VOCATIONAL EDUCATION PROGRAMMES IN SOUTH-SOUTH NIGERIAN UNIVERSITIES - Edokpolor, James Edomwonyi; Dumbiri, David Nwanna (Journal of Vocational Education Studies, 2019)
This study investigated the level of physical facilities adequacy and instructional resources utilization for teaching and learning effectiveness in Technical and Vocational Education and Training (TVET) programmes. A quantitative research design was used, with a sample of 700 participants (85 lecturers and 615 students) which was randomly selected across three Federal Universities in South-South, Nigeria. Structured questionnaires were used to collect data from TVET lecturers and students. Mean, standard deviation and t-test were used for data analyses. Physical facilities were found to be inadequate for teaching and learning processes in TVET programmes. Also, instructional resources were found to be underutilized during teaching and learning in TVET programmes. One of the recommendations made for the study is that TVET managers should endeavour to collaborate with major stakeholders for the provision of funds that would assist in ensuring adequate provision of physical facilities for effective teaching and learning processes in TVET programmes. As such, this would further help to foster the conducive environment for teaching and learning of TVET courses, which in turn, would help in equipping students with the skills to pursue entrepreneurial careers and lifelong learning upon graduation.